Beyond Realism and Marxism - Linklater, A. author. aut Link
VIII, 205 p.
Keywords: This book discusses the challenge to realism which proponents of international political economy and critical theory have mounted in the last few years, and examines the changing relationship between realism and Marxism. It is aimed at students of approaches to international relations.